The long genesis of art appreciation in Quebec’s francophone schools 1876-2000: interview with Suzanne Lemerise - Trudel, Mona (2025)
This article features an interview with Suzanne Lemerise, historian of art education in Quebec, and examines the place of art appreciation in Quebec schools from 1876 to 2000. Lemerise begins with a portrait of the Quebec school system, dominated by religious communities until 1964, in which culture was mainly accessible to students attending private classical colleges. The teaching of drawing in public schools was practical (geometric observation, decoration) and aimed to train workers who would contribute to the development of an emerging modern industrial society. It then presents contextual elements (modern art and psychological theories of child development) as well as various initiatives that contributed to the transition from a simple interest in art, to child-centered teaching of the visual arts, and to the presence of the first written traces of the term appreciation, in the 1970s. The article sheds light on the issues encountered and the agents of change who, through their power of persuasion and the development of teaching materials, contributed to the emergence of appreciation practices as we know them today in Quebec school curricula.